Influence of graphite on the hardness and wear behavior of AA6061-B4C composite - Prabagaran, Subramaniam (Materiali in tehnologije, 2014)
Dry-sliding-wear behavior of AA6061, AA6061-B4C composite and AA6061-B4C-Gr hybrid composite was investigated by employing a pin-on-disc wear-test rig. Hardness tests were also carried out. Graphite was used as a solid lubricant since it is a soft, slippery and greyish-black substance. Because of the cleavage (crystal) loose interlamellar coupling, graphite has good lubricating properties. A comparative analysis was made on the hardness and wear behavior of AA6061, AA6061-B4C composite and AA6061-B4C-Gr hybrid composite. Boron carbide is known as a robust material having a high hardness. Worn-out surfaces of the wear specimens after the wear tests were examined with a scanning electron microscope to study the morphology of the worn surfaces. Energy dispersive spectroscopy (EDS) was employed to identify the oxides formed on the worn surfaces of the AA6061-B4C and AA6061-B4C-Gr composites after the wear test. It was found that a mutual transfer of the material between the wearing Al-alloy and the steel counterface occurred as the load increased. Oxidative wear occurred at low applied loads and a high velocity, whereas delamination and adhesive wear occurred at a high load and high sliding velocity.
Keywords: boron carbide; borov karbid; drsenje; sliding; grafit; graphite; obraba; pin-on-disc; wear resistance; odpornost